2020
DOI: 10.1002/pd.5641
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal diagnosis for Duchenne muscular dystrophy based on the direct haplotype phasing

Abstract: Objective We aimed to investigate the validity of noninvasive prenatal diagnosis (NIPD) based on direct haplotype phasing without the proband and its feasibility for clinical application in the case of Duchenne Muscular Dystrophy (DMD). Methods Thirteen singleton-pregnancy families affected by DMD were recruited.Firstly, we resolved maternal haplotypes for each family by performing targeted linked-read sequencing of their high molecular weight DNA, respectively. Then, we identified SNPs of the DMD gene in all … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
(15 reference statements)
0
15
1
Order By: Relevance
“…We managed haplotype phasing of sequences with a mean length of 129 kb around the expansions in 23/28 parents. The phase block size across the target region was smaller compared with the studies by Chen et al 18 and Lee et al 10 who reported phase blocks with of a mean size of 741 and 632 kb, respectively. Their higher phasing success was mainly due to the larger width of the targeted sequencing region (657 kb and 3.2 Mb, respectively).…”
Section: Discussioncontrasting
confidence: 67%
“…We managed haplotype phasing of sequences with a mean length of 129 kb around the expansions in 23/28 parents. The phase block size across the target region was smaller compared with the studies by Chen et al 18 and Lee et al 10 who reported phase blocks with of a mean size of 741 and 632 kb, respectively. Their higher phasing success was mainly due to the larger width of the targeted sequencing region (657 kb and 3.2 Mb, respectively).…”
Section: Discussioncontrasting
confidence: 67%
“…It affects 1 in 3500 newborn males. The onset usually occurs in early childhood before the age of three and patients rarely outlive the age of twenty [3][4][5]. The development of NIPT techniques for Duchenne muscular dystrophy as an X-linked disease presented a substantial challenge as a consequence of high levels of maternally derived mutant alleles that outnumber potentially mutated alleles of fetal origin in maternal plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, NIPD is almost no risk for the pregnant women and fetuses, and has been gradually applied in fetal aneuploidy, monogenic diseases, sex-linked genetic diseases, and so on ( Xu et al, 2015 ; Drury et al, 2016 ; Guseh, 2020 ). In recent years, haplotype-based NIPD has been reported to be able to deduce the inheritance status of variants in fetuses accurately ( Hui et al, 2017 ; Ma et al, 2017 ; Chen et al, 2020 ). However, NIPD of FSHD1 has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%